Investigating the Function of Hemogen during Erythroid Differentiation - Zhang, Cathy Xin Yue (University of Ottawa (Canada), 2010)
Hemogen is a murine protein expressed in active sites of hematopoiesis during embryogenesis and in the adult. Hemogen's function has not been clearly elucidated. Evidences suggest Hemogen's role in erythroid differentiation. Hemogen expression coincides with active sites of erythropoiesis. beta-globin expression is a hallmark of erythroid differentiation. Proteomic data suggests that Hemogen associates with MafK which is part of the NF-E2 complex that acts as an activator of beta-globin during erythroid differentiation. To gain insight into Hemogen's mechanistic function during erythroid differentiation, we attempted to decipher Hemogen's associating proteins during erythroid differentiation. We generated a Hemogen antibody functional in Hemogen immunoprecipitation (IP). We performed Hemogen IP and used mass spectrometry to identify putative Hemogen interacting proteins within the Hemogen IP elution. Our immuno-fluorescence microscopy (IFM) images of endogenous Hemogen revealed Hemogen as a nuclear protein within murine erythroleukemia cells before and after differentiation. In line with our IFM images, the majority of candidates identified within our putative list of Hemogen associating proteins are transcription regulators. Hemogen expression progressively increased with erythroid differentiation. Hence, Hemogen may function as a transcriptional regulator during erythroid differentiation.
Keywords: Biology, Molecular.